Ultrasound-guided phrenic sparing block in proximal humerus surgery – An observational study - Lahiri, Swati; Asim Kumar Kundu; Manjushree Ray; Rhituparna Bakshi (Asian Journal of Medical Sciences, 2024)
Background: Traditional interscalene brachial plexus block of C5 and C6 roots provides excellent anesthesia and analgesia for shoulder surgery and proximal humerus surgery, but frequently results in hemidiaphragmatic paresis. Superior trunk block (STB) along with local infiltration to supraclavicular nerve branches gives equal analgesic potency and distribution as interscalene brachial plexus block without affecting the phrenic nerve. The present study was carried out on 30 patients undergoing shoulder and proximal humerus surgery under STB of brachial plexus. Aims and Objectives: This study was designed to evaluate the incidence of hemidiaphragmatic paralysis and minimum numerical rating scale (pain score) at rest in the post-anesthesia care unit, block duration, and patients’ satisfaction in patients receiving STB along with local infiltration to supraclavicular nerve branches. Materials and Methods: Thirty patients undergoing shoulder and proximal humerus surgery between 18 and 80 years age group with the American Society of Anesthesiologists-Physical Status I-III of either sex were given ultrasound-guided STB (15 mL) along with a local infiltration (5 mL) superficial to scalenus medias muscle using 0.5% ropivacaine. Primary outcomes and secondary outcomes (patients’ satisfaction, block duration, and pain score) were recorded and analyzed by the Statistical Package for the Social Sciences version 26. Results: Mean sensory block duration (hours) was 16.99±1.27 (95% confidence interval [16.51–17.47]). Incidence of hemidiaphragmatic palsy was minimum (3.3%). Post-operative analgesia was good as reflected by 28 (93.33%) patients having Visual Analog Scale score <3 at 24 h after completion of surgery. Patient satisfaction was also excellent (Likert scores 4 and 5 in 93.33% of patients). Conclusion: STB along with local infiltration superficial to scalenus media’s muscle is associated with excellent intraoperative anesthesia and analgesia with minimal respiratory complication and remarkable patient satisfaction.